A randomised control trial on the use of bioinstrumentation and rehabilitation technology in hemiplegic patients (Journal of Pharmaceutical Negative Results, 2022)
Stroke is a serious cerebrovascular disease characterized by sudden and acute onset and rapid neurological deficits, which is the world’s leading cause of disability and the second leading cause of death, leaving 80% of patients having varying degrees of lifetime neurological deficits. As the global aging problem is getting worse, the positive correlation between stroke and age means that the incidence of stroke will only continue to rise. Stroke incidence is also trending toward even younger patients due to factors such as irregular work life and infrequent rest, a growing sense of pressure and anxiety, poor eating habits, and many other reasons. Hemiplegia is one of the most common symptoms of stroke and significantly affects the patient’s quality of life by reducing their ability to perform activities of daily living. While the rehabilitation of hemiplegic stroke patients has commanded considerable attention in society and medicine, a severe shortage of rehabilitation therapists leads to inconsistent traditional rehabilitation training results. Thus, new treatments borne out of interdisciplinary medicine and engineering methods offer the potential to provide superior care for hemiplegic stroke patients. Such methods can not only promote the recovery of the patient by stimulating nerve remodeling, but also reduce physician workload. Bioinstruments use a variety of measurement modalities that are combined in a robotic hardware-based real-time acquisition and control environment and interpreted with the help of a computational model.